Panggilan Gereja Untuk Misi Amanat Agung di Era 4.0 - Tarigan, Daulat (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Carrying out the mission of the great commission is a general church task, which must be carried out by all believers. Conducting missions in the 4.0 era is a challenge in itself, and the church must empower God's people with the gift of the Holy Spirit who can answer the needs of mission services in this era. The article is qualitative research literature, applying descriptive and phenomenological methods to show a description of service needs related to mission in the 4.0 era. As a result, a leader, in this case, the pastor, must first be empowered in terms of gifts so as to optimize the gifts that are in the church. Keywords: Great commission; 4.0 eras; church congregation.